Temporal trends and risk factors for healthcare-associated vancomycin-resistant enterococci in adults. Issue 3 (November 2016) - Monteserin, N.; Larson, E.
Summary: Background: Published data regarding temporal trends in vancomycin-resistant enterococci (VRE) prevalence within specific regions or healthcare systems are scarce. Aim: To characterize temporal trends and risk factors for healthcare-associated infections caused by VRE. Methods: The study included all adult discharges occurring from 2006 to 2014 with an enterococcal infection from three hospitals in a large academic healthcare system. Bivariate analyses were used to identify statistically significant factors associated with vancomycin-susceptible or -resistant infection. Statistically significant variables were included in a final logistic regression model. Trends assessed whether the proportion of enterococcal infections resistant to vancomycin changed over time. Findings: The sample included 10, 186 adults with first-time healthcare-associated enterococcal infection. Significant risk factors ( P  ≤ 0.05) for VRE in the final logistic regression model included: tertiary 1 hospital, intensive care unit length of stay, higher Charlson Comorbidity Index, previous immunosuppressive or chemotherapeutic medications, previous hospitalization, renal failure, malignancy, longer length of stay prior to infection, taking an antibiotic prior to infection, being female, and having an infection in winter or spring. Between 2006 and 2014, the rate of resistance varied from 37.1 to 42.9% but there were no significant differences in the proportion resistant to vancomycin over time ( P  = 0.36). Conclusion: Research targeted at risk factors is important to decrease the amount of VRE infections.